Cointegration and causality of stock markets in two small open economies and their major trading partner nations - Markku Malkamäki (Bank of Finland, 1992)
This paper examines eointegration and Granger eatisality among the stock markets in the United States, the United Kindom, Germany, Sweden and Finland. The first three nations are the biggest trading partners of the two small open Nordie eeonomies, Finland and Sweden. We apply standard univariate VAR models and a system of VAR models under the assumption of multivariate eointegration, first introdueed in Johansen (1988). Our results from eausality analysis eontradiet the prior understanding with respect to the eausal relations between the Nordie and other stoek markets. Our multivariate eointegration analysis suggests that the stoek markets are cointegrated with one eointegrating veetor when prices are measured in IoeaI eurrencies or in Finnish markkas and two eointegrating vectors when prices are measured in US dollars. The Finnish stoek market is always found to be led by the German market, and aIso by the UK market when returns are measured in IoeaI eurreneies or in Finnish markkas. We also found that the Swedish stoek market is Granger eaused by the UK market instead of the US market as previously suggested. The data covers the period 1974-1989.
URN:NBN:fi:bof-201808021853
Keywords: 330